Potential for the Rational Design of Allosteric Modulators of Class C GPCRs - A. Christopher, John; S. Doré, Andrew; G. Tehan, Benjamin (Current Topics in Medicinal Chemistry, 2017)
Class C G protein-coupled receptors encompass a range of promising therapeutic targets for a variety of diseases, yet to date only two members of this sub-family of GPCRs have been drugged. Recent advances in structural biology have revealed the X-ray crystallographic structures of allosteric ligands bound to two Class C metabotropic glutamate (mGlu) receptors, mGlu1 and mGlu5. Herein, we review how this information can be leveraged to help understand some of the historical challenges of mGlu receptor allosteric modulator drug discovery, and discuss how the structural enablement can be prospectively used for structurebased drug discovery approaches across Class C GPCR targets in general.
Keywords: CNS